Visiones y versiones decimonónicas de la Independencia peruana - Chocano, Magdalena (2022)
This article examines the chronology-building of Peruvian Independence based on calendars published between 1821 and 1840. It also analyzes different approaches to the Independence process by authors like Valdez y Palacios, Pruvonena (Riva Agüero), S. Távara, C. Lissón, S. Lorente, M. F. Paz Soldán, and Rodríguez. Their writings show a diversity of solutions to the ambiguity that marked the process and their efforts to enclose it within an unambiguous and continuous temporal sequence.